Multiplatform Metabolomics Studies of Human Cancers With NMR and Mass Spectrometry Imaging - Zhong, Anya B.; Muti, Isabella H.; Eyles, Stephen J.; Vachet, Richard W.; Sikora, Kristen N.; Bobst, Cedric E.; Calligaris, David; Stopka, Sylwia A.; Agar, Jeffery N.; Wu, Chin-Lee; Mino-Kenudson, Mari A.; Agar, Nathalie Y. R.; et al. (Frontiers in Molecular Biosciences, 2022)
The status of metabolomics as a scientific branch has evolved from proof-of-concept to applications in science, particularly in medical research. To comprehensively evaluate disease metabolomics, multiplatform approaches of NMR combining with mass spectrometry (MS) have been investigated and reported. This mixed-methods approach allows for the exploitation of each individual technique’s unique advantages to maximize results. In this article, we present our findings from combined NMR and MS imaging (MSI) analysis of human lung and prostate cancers. We further provide critical discussions of the current status of NMR and MS combined human prostate and lung cancer metabolomics studies to emphasize the enhanced metabolomics ability of the multiplatform approach.